Regulation of Stress-Induced Immunosuppression in the Context of Neuroendocrine, Cytokine, and Cellular Processes - Evgenii Balakin; Ksenia Yurku; Mark Ivanov; Alexander Izotov; Valeriya Nakhod; Vasiliy Pustovoyt (Biology)
Understanding the regulatory mechanisms of stress-induced immunosuppression and developing reliable diagnostic methods are important tasks in clinical medicine. This will allow for the development of effective strategies for the prevention and treatment of conditions associated with immune system dysfunction induced by chronic stress. The purpose of this review is to conduct a comprehensive analysis and synthesis of existing data on the regulatory mechanisms of stress-induced immunosuppression. The review is aimed at identifying key neuroendocrine, cytokine, and cellular processes underlying the suppression of the immune response under stress. This study involved a search of scientific literature covering the neuroendocrine, cellular, and molecular mechanisms of stress-induced immunosuppression regulation, as well as modern methods for its diagnosis. Major international bibliographic databases covering publications in biomedicine, psychophysiology, and immunology were selected for the search. The results of the analysis identified key mechanisms regulating stress-induced immunosuppression. The reviewed publications provided detailed descriptions of the neuroendocrine and cytokine processes underlying immune response suppression under stress. A significant portion of the data confirms that the activation of the hypothalamic–pituitary–adrenal (HPA) axis and subsequent elevation of cortisol levels exert substantial immunosuppressive effects on immune cells, particularly macrophages and lymphocytes, leading to the suppression of innate and adaptive immune responses. The data also highlight the crucial role of cortisol and catecholamines (adrenaline and noradrenaline) in initiating immunosuppressive mechanisms under chronic stress.